Sociomuseology and Cultural Accessibility: contemporary provocations from the Round Table of Santiago (Chile) (Cadernos de Sociomuseologia, 2023)
This article presents the result of the reflections and propositions of the Study Group ‘Sociomuseology and Cultural Accessibility’ and this publication is part of the context of commemoration of the fiftieth anniversary of the Round Table of Santiago (Chile), an important historical landmark in Sociomuseology. We propose a provocative reflection on this event, from the perspective of Cultural Accessibility. The Study Group is formed by a group of researchers from the Master's and Doctoral course in Sociomuseology at the Universidade Lusófona (UL) in Lisbon and has the participation of external researchers not linked to the ULHT, but who work with the themes related. The creation of the group was motivated to bring to the aforementioned Department issues related to accessibility and ableism, which is the existing social prejudice in relation to people with disabilities. The text brings to the discussion theoretical references from studies on Science, Technology and Society (STS studies) in order to understand how these researches contribute to accessibility and can advance their discussions.Key words: Cultural Acessibility; Sociomuseology; Capacitism; Round Table of Santiago (Chile); Museology.